Buenas prácticas de turismo sostenible y calidad del servicio turístico en el distrito de Nauta 2021 - Yuyarima Tina, Clauver (2023)
The research had as general objective: to determine the relationship between good practices of sustainable tourism and quality of the tourist service in the District of Nauta 2021, where an applied type study was chosen, descriptive-correlational level with non-experimental design, which It was made up of a population of 126,000 tourists, taking the sample of 368 tourists, to whom the survey technique and the questionnaire of questions were applied as an instrument for data collection. Concluding that good sustainable tourism practices are being developed on a regular basis (32%). For its part, the quality of tourist service is rated as regular (31%). Regarding the relationship, it was determined that there is a significant relationship between good practices of sustainable tourism and the quality of the tourist service corroborated by (r=0.739; p=0.000), the same for the environmental axis dimension (r=0.501; p=0.000); for the socioeconomic axis (r=0.717; p=0.000) and the tourist axis (r=0.542; p=0.000) all are significantly related to the quality of the tourist service.